Stress and strain evolution in fault-related folds: insights from 2D geomechanical modelling - Khalifeh-Soltani, Anis; Alavi, Seyed Ahmad; Ghassemi, Mohammad Reza; Derakhshani, Reza (Frontiers in Earth Science, 2023)
Fault-related folds are intriguing geological structures that develop in compressional and extensional regimes. These folds serve as structural traps for hydrocarbon resources, making their numerical models crucial for understanding the stress and strain evolution of hydrocarbon reservoirs. In our research, we utilize the two-dimensional finite element technique to simulate three representative categories of fault-related folds. Our investigation encompasses their geometric transformation over time, the distribution of stress and strain, variations in slip and uplift, and the effects that various mechanical properties have on these gradients. In our study, we uncovered essential findings about the behavior of fault-related folds. We ascertained that the fault slip gradient in the fault-bend fold model is less than in the fault-propagation fold model. Regarding the uplift gradient, the fault-propagation and fault-bend fold models displayed the greatest and the least degree of change, respectively. The trend of stress-strain evolution on the fold surface in all models was consistent, starting with an increase, transitioning to a constant phase, and ending with a decrease. This pattern proved to be more intricate and divergent than what was evident on the fault surface. Importantly, the internal friction angle, a crucial mechanical characteristic, had a significant influence on the development of these structures. This angle affected both the degree of uplift and stress; an increased angle resulted in enhanced uplift and stress, while a decrease resulted in a decline. Furthermore, the internal friction angle determined the compactness of the fold and the thickness of the forelimb, the part of the fold that inclines towards the advancing direction. These findings have enriched our knowledge of fault-related folds, highlighting the need to consider mechanical properties when studying their formation and evolution.